Interfacial Engineering for High-Output, Mechanically Robust Fully Stretchable Moisture-Electric Generators - Meng, Qi; Zhang, He; Feng, Jiayun; Yu, Minghan; Sun, Yuxin; Wang, Shujun; Sun, Yuxiang; Sun, Mingze; Xu, Jie; Xie, Haijiao; Sun, Qing; Tian, Yanhong (Nano-Micro Letters, 2026)
Fully stretchable hydrogel-based moisture-electric generators (FSHMEGs) are promising power sources for wearable and implantable electronics. Current FSHMEGs are constrained by low electrical output and mechanical fragility, mainly due to weak interfacial adhesiveness within multilayered architectures. Here, we introduce an intrinsically adhesive hydrogel that forms robust hydrogel-electrode interfaces, enabling efficient transfer of both electrical charges and mechanical loads during deformation. As a result, the device delivers an open-circuit voltage of 0.94 V and a current density of 141 µA cm−2 at 85% relative humidity, and maintains stable output for more than 220 h. The reinforced interface also imparts exceptional mechanical durability, exhibiting only negligible performance degradation after 8000 folding cycles and 1000 stretching cycles at 80% strain. Benefiting from rapid humidity responsiveness and continuous power delivery, the device enables non-invasive respiration monitoring and can directly power wearable electronics (e.g., electrocardiogram (ECG) sensors). This interfacial-engineering strategy offers a practical pathway toward high-performance moisture-electric generators with broad potential in energy harvesting, bioelectronics, and self-powered sensing systems. Hightlights: 1 Introduces an intrinsically adhesive interfacial engineering strategy for hydrogel-based moisture-electric generators, enabling simultaneous enhancement of electrical output and mechanical robustness. 2 Reveals the mechanism of enhanced interfacial charge transfer and suppressed delamination through electrochemical impedance spectroscopy analysis, ab initio molecular dynamics/density functional theory simulations, and mechanical characterization. 3 Achieves long-term operational stability (220 h) and exceptional mechanical durability (8000 folding cycles and 1000 stretching cycles at 80% strain), with successful demonstrations in wearable respiration monitoring and electrocardiogram powering.